Variation in Feeding Behaviour of Nilaparvata lugens on Resistant and Susceptible Rice Varieties - Cook, A.G.; Woodhead, S.; Magalit, V.F.; Heinrichs, E.A. (Wiley, 1987)
The feeding behaviour of Nilaparavata lugens was monitored on three rice varieties showing different levels of resistance in the Philippines, using a video‐assisted observation method. N. lugens made more frequent, shorter probes on the moderately resistant IR46 and resistant IR62 rice varieties than on the susceptible IR22. Honeydew production was significantly lower on the resistant varieties though insect weight gains in 24 h were similar on IR46 and IR22, both being significantly greater than on the highly resistant variety.Population development, growth index and damage ratings were low on IR62 indicating antibiosis and/or non preference. When IR46 plants were infested as seedlings population increase, growth index and damage ratings were similar to those on the susceptible IR22. When infested at a later stage of plant growth the damage rating showed a moderate level of resistance though some population development was maintained, indicating antibiosis and tolerance.N. lugens started probing less frequently after surface exploration on both resistant varieties than on IR22 suggesting the presence of a resistance factor associated with the surface waxes of these varieties.